IDENTIFIKASI MAKANAN BERPROTEIN SEBAGAI UPAYA PENCEGAHAN STUNTING PADA SISWA SEKOLAH DASAR DI PULAU NUNUKAN - Ananda, Yosep Yuswanto Tri; Samsidar; Rohman Nasrudin, Abdul; Partogi Hasudungan Sinaga, Samuel; Ilham; Alamsyah, MIsdar; Fazli, Akhmad; Luthfiyah, Mardhiyatul; Iswan, Muhammad (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
The purpose of this activity is to educate elementary school students about stunting through learning activities with simple practical activities. In this activity, the speaker provided two materials. First, delivering material about stunting and how to prevent it. Second, inviting participants to get to know various foods that contain protein and do simple lab work. The practical activity carried out was a protein test using vinegar acid. The participants gained an understanding of stunting, protein foods, and new learning experiences through practical activities. The results of the response questionnaire showed that all students (100%) were happy with the learning model provided by the speaker. It is hoped that education about stunting through the consumption of protein foods like this can reach all levels of society from an early age.